The Degree of Application of Quality Standards for Inclusive Education/ New Jersey Coalition for Inclusive Education (NJCIE) in Inclusive Education Schools in Jordan - Bani Khaled, Ibrahim Bani; Al-Adamat, Omar (Dirasat: Educational Sciences, 2024)
Objective: The current study aimed to examine the degree of applicability of the standards of the New Jersey Alliance for Inclusive Education (NJCIE) in public and private schools applying inclusive education programs in Jordan from the point of view of teachers. Methods: The study used an analytical descriptive method. A study scale was also built according to the standards and indicators of NJCIE. The study sample consisted of (125) male and female teachers who are working in these schools, and who were purposively selected. Results: The results of the study indicated that the total degree of application of the Standards of Quality Standards for Inclusive Education / NJCIE in inclusive education schools in Jordan was medium, and it was higher for the field of school climate with a high degree, and the lowest for the field of professional practices with a medium degree. The results also showed that there were no statistically significant differences in the level of application of quality standards for inclusive education / NJCIE in inclusive education schools in Jordan due to gender (teacher) or school type (public / private). Conclusions: The study recommended that the responsible authorities adopt clear and specific criteria and develop an accountability and follow-up system to control the quality of services provided in inclusive schools. It also recommended conducting more studies on centers and schools while determining the type of disability considering different variables and perspectives.